The review of Bulbophyllum section Tripudianthes (Orchidaceae) in the flora of Vietnam with the description of new species, B. viridipallidum - Nguyen, van Canh; Averyanov, Leonid V.; Maisak, Tatiana V.; Nguyen, Thi Lien Thuong; Nguyen, van Khuong; Pham, Thi Thanh Dat; Nguyen, Danh Duc; Dang, van Son; Aromyen, Warapong; Truong, Ba Vuong (Phytotaxa, 2023)
The paper provides a short annotated taxonomic review of Bulbopyllum sect. Tripudianthes from the flora of Vietnam along with a species-level key for identification. The section in Vietnam includes five species, one of which is a new species for science and described under the name, B. viridipallidum. The new species was found recently from Kon Tum Province of southern Vietnam. It is similar to B. kanburiense, B. khaoyaiense, and B. wallichii, but clearly differs by having pale greenish lateral sepals and two rounded calli at the lip base fused distally into a single prominent longitudinal keel; this is inflated at the lip apex into prominent half ovoid callus. In addition, we confirm the occurrence of B. wallichii in the flora of Vietnam. The taxonomic description, data on distribution, ecology, phenology, proposed conservation status, taxonomic notes, and the comparison of the new species with morphologically similar species are reported.